Diabetic Polyneuropathy Is Associated With Pathomorphological Changes in Human Dorsal Root Ganglia: A Study Using 3T MR Neurography - Jende, Johann M. E.; Kender, Zoltan; Rother, Christian; Alvarez-Ramos, Lucia; Groener, Jan B.; Pham, Mirko; Morgenstern, Jakob; Oikonomou, Dimitrios; Hahn, Artur; Juerchott, Alexander; Kollmer, Jennifer; Heiland, Sabine; et al. (Frontiers in Neuroscience, 2020)
Diabetic neuropathy (DPN) is one of the most severe and yet most poorly understood complications of diabetes mellitus. In vivo imaging of dorsal root ganglia (DRG), a key structure for the understanding of DPN, has been restricted to animal studies. These have shown a correlation of decreased DRG volume with neuropathic symptom severity. Our objective was to investigate correlations of DRG morphology and signal characteristics at 3 Tesla (3T) magnetic resonance neurography (MRN) with clinical and serological data in diabetic patients with and without DPN. In this cross-sectional study, participants underwent 3T MRN of both L5 DRG using an isotropic 3D T2-weighted, fat-suppressed sequence with subsequent segmentation of DRG volume and analysis of normalized signal properties. Overall, 55 diabetes patients (66 ± 9 years; 32 men; 30 with DPN) took part in this study. DRG volume was smaller in patients with severe DPN when compared to patients with mild or moderate DPN (134.7 ± 21.86 vs 170.1 ± 49.22; p = 0.040). In DPN patients, DRG volume was negatively correlated with the neuropathy disability score (r = −0.43; 95%CI = −0.66 to −0.14; p = 0.02), a measure of neuropathy severity. DRG volume showed negative correlations with triglycerides (r = −0.40; 95%CI = −0.57 to −0.19; p = 0.006), and LDL cholesterol (r = −0.33; 95%CI = −0.51 to −0.11; p = 0.04). There was a strong positive correlation of normalized MR signal intensity (SI) with the neuropathy symptom score in the subgroup of patients with painful DPN (r = 0.80; 95%CI = 0.46 to 0.93; p = 0.005). DRG SI was positively correlated with HbA1c levels (r = 0.30; 95%CI = 0.09 to 0.50; p = 0.03) and the triglyceride/HDL ratio (r = 0.40; 95%CI = 0.19 to 0.57; p = 0.007). In this first in vivo study, we found DRG morphological degeneration and signal increase in correlation with neuropathy severity. This elucidates the potential importance of MR-based DRG assessments in studying structural and functional changes in DPN.